1983
DOI: 10.1104/pp.72.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sulfate Transport Across Plasmalemma and Tonoplast of Carrot Root Cells

Abstract: Compartmental analysis of "SO4-2 exchange kinetics is used to obtain S042-fluxes and compartment contents in carrot (Daucus carota L.) storage root cells, where 2 to 5% of the S042-taken up is reduced to organic form. The necessary curve fit is verified by (a) consistency between 'content versus time' and 'rate versus time' plots of washout data; (b) agreement between loading and washout kinetics; and (c) correct identification of the fastest exchange phase as being from extracellular spaces.Sulfate is activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…1B), as has been reported for tomato (Solanum lycopersicum) seedlings and carrot (Daucus carota) storage root sections (Cram, 1983;Lopez et al, 2002). In carrot, Cram et al (1983) showed a proportional increase up to an external concentration of 50 mM, leading the authors to conclude that feedback inhibition of sulfate uptake is absent. Vegetative root growth was less affected by alterations in available sulfate concentrations than was uptake or reduction (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…1B), as has been reported for tomato (Solanum lycopersicum) seedlings and carrot (Daucus carota) storage root sections (Cram, 1983;Lopez et al, 2002). In carrot, Cram et al (1983) showed a proportional increase up to an external concentration of 50 mM, leading the authors to conclude that feedback inhibition of sulfate uptake is absent. Vegetative root growth was less affected by alterations in available sulfate concentrations than was uptake or reduction (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…However, in the absence of measurable ARAC-mediated citrate or malate efflux in this study and the absence of ARAC regulation by phosphate supply (see below) or by extracellular Cu 21 (data not shown), it is unlikely that ARAC is responsible for organic-acid efflux from Arabidopsis roots. Although it has received far less attention than organic-acid anions, inorganic anion efflux has also been recorded from higher plant roots, for example Cl 2 efflux from barley (Jackson and Edwards, 1966) and Arabidopsis (Lorenzen et al, 2004) and SO 4 22 efflux from carrot (Cram, 1983) and tomato roots (Lopez et al, 2002). The physiological significance of these fluxes is not always clear, but they may be important in preventing the toxic accumulation of anions in the cytosol of root cells, particularly when extracellular anion concentration is high.…”
Section: Physiological Significance Of Aracmentioning
confidence: 99%
“…For use with intact plant material, a detailed treatise on parameter extraction was presented by Jeschke and Jambor (1981) and Jeschke (1982). More recently, compartmental analysis has also been applied to metabolized ions, including S0,2p (Thoiron et al, 1981;Cram, 1983; Bell et al, 1994), Pi (Lefebvre and Clarkson, 1984;Macklon and Sim, 1992), NO,-(Presland and McNaughton, 1984 1986; Macklon et al, 1990;Siddiqi et al, 1991;Devienne et al, 1994;Kronzucker et al, 1995a Kronzucker et al, , 1995b, and NH,+ (Presland and McNaughton, 1986;Cooper et al, 1989;Macklon et al, 1990;Wang et al, 1993a;Kronzucker et al, 1995~). Despite this widespread use of the technique, workers have typically neglected to conduct physiological tests to verify the subcellular identities of the phases revealed in efflux data.…”
mentioning
confidence: 99%
“…For use with intact plant material, a detailed treatise on parameter extraction was presented by Jeschke and Jambor (1981) and Jeschke (1982). More recently, compartmental analysis has also been applied to metabolized ions, including S0,2p (Thoiron et al, 1981;Cram, 1983;Bell et al, 1994), Pi (Lefebvre and Clarkson, 1984;Macklon and Sim, 1992), NO,- (Presland and McNaughton, 1984;Lee and Clarkson, The work reported in this paper was supported by a National Sciences and Engineering Research Council of Canada grant to A.D.M.G. and by a University of British Columbia Graduate Fellowship to H.J.K.…”
mentioning
confidence: 99%